2017
DOI: 10.1016/j.aorn.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Temporary Perioperative Tobacco Cessation: A Literature Review

Abstract: Perioperative tobacco cessation decreases rates of surgical complications associated with the use of tobacco. The link between patient outcomes and reimbursement to health care providers and systems is another important motivating factor supporting temporary pre- and postoperative tobacco cessation to improve surgical patient outcomes. The optimal time frame for tobacco cessation to improve surgical outcomes has not been definitively established. We examined the literature from June 1989 to July 2017 regarding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“…Among 12,062 patients undergoing bariatric surgery in Western Australia, anesthetic complications were uncommon (0.5%) but accounted for 9.7% of all ICU postoperative readmissions, of which, smoking history (and not BMI) was the only prognostic factor for airway‐related complications . All smokers must be advised to stop smoking at any time before bariatric surgery, even if it is within 6 weeks before surgery . Unfortunately, in a retrospective review of the NSQIP database, Haskins et al found that smoking within the year before SG was associated with increased 30‐day morbidity and mortality risk, compared with nonsmokers.…”
Section: Executive Summarymentioning
confidence: 99%
“…Among 12,062 patients undergoing bariatric surgery in Western Australia, anesthetic complications were uncommon (0.5%) but accounted for 9.7% of all ICU postoperative readmissions, of which, smoking history (and not BMI) was the only prognostic factor for airway‐related complications . All smokers must be advised to stop smoking at any time before bariatric surgery, even if it is within 6 weeks before surgery . Unfortunately, in a retrospective review of the NSQIP database, Haskins et al found that smoking within the year before SG was associated with increased 30‐day morbidity and mortality risk, compared with nonsmokers.…”
Section: Executive Summarymentioning
confidence: 99%
“…Among 12,062 patients undergoing bariatric surgery in Western Australia, anesthetic complications were uncommon (0.5%) but accounted for 9.7% of all ICU postoperative re-admissions, of which, smoking history (and not BMI) was the only prognostic factor for airwayrelated complications (474). All smokers must be advised to stop smoking at any time before bariatric surgery, even if it is within 6 weeks before surgery (475). Unfortunately, in a retrospective review of the NSQIP database, Haskins et al (314) found that smoking within the year before SG was associated with increased 30-day morbidity and mortality risk, compared with nonsmokers.…”
Section: R23 (2019*)mentioning
confidence: 99%
“…In a recent systemic review, smoking during a year before undergoing surgery, was an independent risk factor for higher 30 d mortality and major postoperative complications, particularly wound and pulmonary complications[ 107 ]. Perioperative tobacco cessation reduces the chance of surgery-related morbidities[ 108 ]. A structured program is more effective than general advice[ 109 ].…”
Section: Preoperative Evaluation and Optimization Of Pulmonary Functionmentioning
confidence: 99%